Novel antibacterial therapy : mechanical force and light-activation - Du, Quanchao (Nanyang Technological University, 2021)
This thesis focuses on the design and development of novel antimicrobial nanoplatform to combat bacterial infections. We have designed and characterized several new nanoplatforms by integrating multiple materials such as nanoparticles, polymers, organic molecules and antibiotics to combat different types of bacteria. Chapter 1 provides a general introduction to antibacterial therapy including two strategies, one is drug-based antibacterial strategy, the other one is nanoparticle-based antibacterial strategy. For nanoparticle-based antibacterial strategy, nanoparticles serving as vehicles for drug delivery and nanoparticles with intrinsic antibacterial capacity such as photodynamic and photothermal ability will be introduced. And then attention is given to swarming motility of bacteria and we discuss how the swarming motion occurs and how antimicrobial resistance is induced by swarming motility. In chapter 2, an antibacterial drug release system that is triggered into action upon sensing the motion of swarmer Gram-negative bacteria is introduced. A copolymer (pNIPAAm-co-AEMA) which displays affinity to Gram-negative bacteria, is electrostatically attached to the surface of mesoporous silica particles (drug carriers) in order to seal in the loaded drug, tobramycin. When swarmer P. mirabilis cells approach and come in contact with the particles, the copolymer chains bind to the motile Gram-negative cells and are stripped off the particle surface; hence releasing tobramycin into the swarmer colony and inhibiting its expansion. In chapter 3, an efficient method of bio-conjugating Van to bacteria is proposed using near-infrared (NIR)-light activation. A Nd3+-sensitized upconversion nanocrystal (UCNC) decorated with toluidine blue O (TB) on its surface undergoes upconverted energy transfer from the UCNC to TB when excited by 808 nm light. The photoexcited TB then catalyses the conversion of the dihydrotetrazine (dHTz) moiety in a Van-dHTz conjugate system to tetrazine which undergoes efficient inverse electron demand Diels-Alder reaction with prior attached norbornene molecules on bacterial cell walls. MIC of attached Van is reduced by 6- to 7-fold as compared to neat Van. In chapter 4, an improved photothermal antimicrobial method by conjugating photothermal agents onto bacterial cell wall is designed. Following the conjugating procedure described in chapter 3, ATTO740 is attached onto bacterial cell walls by covalent bonding. This attachment is controllable by switching on/off a 808 nm light source. The enhanced affinity of ATTO740 to bacteria by covalent bonding improves photothermal activity. Bacterial mortality increases ~20% as compared to unattached ATTO740.